Civic Education in Contextual Interpretation through Qur’anic Learning in Pesantren and Schools - Ikhwanudin; Rahardjo; Roselina Ahmad Saufi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Contextual tafsir education serves a strategic role in strengthening Civic Education as an ideological safeguard in the face of globalization and rising radicalism. By connecting the Qur’anic text with social realities, contextual tafsir internalizes national values such as tolerance, social justice, and deliberation, which are aligned with the principles of Civic Education. This study investigates how Qur’anic learning in pesantrens and schools can function as a medium for both Living Qur’an and Living Civic Education, where sacred values are not only textually interpreted but also lived in daily practice. Employing a qualitative approach with literature review and conceptual analysis, the research identifies the integration of Qur’anic values such as tasamuh (tolerance), ‘adl (justice), and syura (deliberation) with the ideals of Pancasila-based Civic Education. The findings indicate that contextual tafsir, when supported by integrative curricula, teacher training, and community participation, effectively nurtures a generation that is religiously grounded, nationally committed, and ethically responsible. The conclusion emphasizes that Islamic religious education should not only cultivate individual piety but also reinforce national identity and serve as a counterforce to exclusivist ideologies. This approach offers a transformative model for character education in Indonesia’s pluralistic context.